2002
DOI: 10.1088/0022-3727/35/23/316
|View full text |Cite
|
Sign up to set email alerts
|

LISA simulations of time-reversed acoustic and elastic wave experiments

Abstract: Several experiments in the last decade have demonstrated the enormous potential of time-reversed acoustic (TRA) and elastic (TRE) waves for applications in many fields, such as medicine, materials characterization and oceanography. In the present contribution, we demonstrate the applicability of the local interaction simulation approach (LISA) to simulate, by means of virtual experiments, both TRA and TRE and to reproduce the relevant features of both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…6,7 Furthermore, the validity of time reversal has been proven in solids. [8][9][10] More recently, Tanter et al 11 and Cunningham et al 12 have proven reversibility in nonlinear elastic media, at least under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Furthermore, the validity of time reversal has been proven in solids. [8][9][10] More recently, Tanter et al 11 and Cunningham et al 12 have proven reversibility in nonlinear elastic media, at least under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…27 In particular, simulations have shown that the energy of the reversed wave field focuses on the scatterers, hence indicating a novel imaging procedure. 9,10,28 In this paper, we suggest a novel procedure to obtain selective focusing on nonlinear scatterers. We also introduce additional novelties with respect to the existing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to examine these ideas using a simplified numerical simulation of the experiment-these results have already been published and are reported elsewhere. 14 In that simulation, we made a first attempt to model and simulate the process numerically using the local interaction method known as LISA. 15 The initial results from that work ͑simu-lating just a few reflections͒ were encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical time reversal for elastic media has been considered in [11,25] while experimental results are reported in [24,21,20]. The DORT (french acronym for decomposition of the time reversal operator) method applied to elastic wave scattering can be found in [4].…”
Section: Introductionmentioning
confidence: 99%